Hiv and Pregnancy - Almond, Brenda (The Hastings Center report, 1990)
Testing women of childbearing age for HIV infection and disclosure of HIV status should be examined from three interlocking perspectives— women's personal concerns, the interests of caregivers, and those of the community. In the absence of specific objections, testing for HIV infection should be considered a routine procedure in prenatal care.